STRATEGI KOMUNIKASI KEPEMIMPINAN DALAM MENINGKATKAN MOTIVASI KINERJA PEGAWAI PADA DINAS PERHUBUNGAN GAYO LUES - Rusnawati, Rusnawati (JURNAL AL-IJTIMAIYYAH, 2020)
The number of employees lacking discipline in entering, leaving work hours, lack of enthusiasm at work, not showing the level of performance at work, and several of these factors occur in the Gayo Lues Transportation Agency. This study aims to determine the Constraints faced by Leaders in Increasing Employee Motivation at the Gayo Lues Transportation Agency, to determine the leadership communication strategy in increasing employee work motivation at the Gayo Lues Transportation Service. This research is a field research (Field research). The method in this research is descriptive method, with a qualitative approach. Data were collected through methods: interviews, observation and documentation. From the results of this study, the authors found that the obstacle to the Department of Transportation was a lack of discipline, lack of facilities and infrastructure and human resource factors, the impact of this made employees appear not to show enthusiasm at work. However, the communication strategy at the Department of Transportation carried out by the leadership with its employees is good even though the communication carried out is not verbal but non-verbal, which is transferred to the Secretary and supported by applicable rules, this rule is applied to part of the strategy of the Gayo Lues Transportation Service. Namely regarding discipline at work, if there are employees who still violate these rules, they will be given sanctions ranging from mild, moderate and severe. Suggestions given by researchers to get maximum results, personal approach must be improved. Without ever differentiating employees from one another which can lead to conflict and jealousy by each employee.Keywords:  Communication Strategy, Leadership, Motivation, and Employee Performance.